Enhancing learners' academic achievements in rural Lesotho schools: matching teaching and learning styles - Letele, Moeketsi Joseph (University of the Free State, 2009)
English: The Lesotho Junior Certificate results between 2003 and 2006 indicate that in the rural secondary schools of Lesotho the pass rate ranged from 51% to 58%. These figures are low compared to those in the urban schools for the same years which ranged from 70% to 72%. The Teaching Service Department shows that there was 40% of unqualified teachers in these schools in 2003 and 35% in 2007. There seems to be a correlation between the high numbers of unqualified teachers and the low pass rate in these schools. This view is underscored by Wheeler and McLeod (2002: 696) who note that teachers are more likely to develop teaching styles which are congruent with their own learning styles rather than those of their learners if they are unaware of the learning and teaching styles literature. This study aims to establish teaching styles that match the learning styles of learners in the rural secondary schools of Lesotho with the view to improve academic achievement. The objectives are: to determine whether teachers in these schools have adequate knowledge pertaining to teaching and learning styles; to identify the predominant styles; to determine the extent to which matching teaching and learning styles improves academic achievement; and to provide a teacher's guide on teaching and learning styles. The research comprises of a literature study and empirical investigation. The Solomon Felder Index of Learning Styles (SFILS) and self-designed teaching style questionnaire were used. The learners' end-of-year examination marks were studied. The empirical findings indicate that most teachers in rural secondary schools of Lesotho do not have adequate knowledge on teaching and learning styles, while findings from the literature and empirical study indicate that academic achievement of learners can be enhanced by matching teaching and learning styles. Therefore, these findings can be used to improve the teaching and learning process and ultimately the level of success that learners in rural secondary schools can experience in their respective schools. Finally, the findings of this study were used to develop a teacher's guide on teaching and learning styles. This would hopefully guide teachers in the rural secondary schools of Lesotho on which styles could work best in their contexts.

Afrikaans: Die uitslae van die Lesotho Junior Sertifikaat dui daarop dat die slaagsyfer in landelike sekondêre skole in Lesotho tussen 2003 en 2006 gewissel het van 51% tot 58%. Hierdie syfers is laag in vergelyking met die uitslae van stedelike skole in die ooreenstemmende tydperk waar uitslae gewissel het van 70% tot 72%. Volgens die Departement van Onderwysdienste was 40% van die onderwysers in hierdie skole in 2003 ongekwalifiseerd. In 2007 was 35% van die onderwysers ongekwalifiseerd. Daar skyn 'n korrelasie tussen die groot getal ongekwalifiseerde onderwysers en die lae slaagsyfer in hierdie skole te bestaan. Hierdie siening word deur Wheeler en McLeod (2002: 696) beaam. Hulle voer aan dat onderwysers geneig is om veel eerder onderrigstyle te ontwikkel wat ooreenstem met hulle persoonlike leerstyle as met die leerstyle van hulle leerders - veral as die onderwysers onkundig is oor die leer- en onderrigstyle wat in die literatuur beskikbaar is. Hierdie studie poog om onderrigstyle daar te stel wat ooreenstem met die leerstyle van die leerders in landelike sekondêre skole in Lesotho met die doel om akademiese prestasie te verbeter. Die doelwitte is: om vas te stelof onderwysers aan hierdie skole oor voldoende kennis van onderrig-en leerstyle beskik; om die oorheersende style te identifiseer; om te bepaal in watter mate 'n korrelasie tussen onderrig- en leerstyle akademiese prestasie verbeter; 'n handleiding vir onderrig-en leerstyle vir onderwysers te ontwikkel. Die navorsing bestaan uit 'n literêre studie en empiriese ondersoek. Die Solomon Felder Indeks van Leerstyle (SFILS) en 'n self-ontwerpte onderrigstylvraelys is gebruik. Die leerders se uitslae vir die eindeksamen is bestudeer. Die empiriese bevindinge dui daarop dat die meeste onderwysers aan landelike sekondêre skole in Lesotho nie beskik oor voldoende onderrig- en leerstyle nie. Bevindinge in die literatuur en empiriese studies dui daarop dat leerders se akademiese prestasie verbeter kan word deur onderrig- en leerstyle met mekaar te korreleer. Daarbenewens kan hierdie bevindinge ook aangewend word om onderrig- en leerproses te verbeter en uiteindelik sal leerders in landelike sekondêre skole meer sukses ervaar. Laastens is die bevindinge van hierdie ondersoek aangewend om 'n onderwyserhandleiding saam te stel wat gebruik kan word ter ontwikkeling van onderrig- en leerstyle. Sodoende salonderwysers in landelike sekondêre skole in Lesotho leiding ontvang oor die mees geskikte style vir hulle unieke situasies.
Keywords: Rural schools; Learning styles; Academic achievement; Teaching styles; Learner -centered; Academic achievement -- Lesotho; Teacher effectiveness -- Lesotho; High school teaching -- Lesotho; Dissertation (M.Ed. (Psychology of Education))--University of the Free State, 2009